Noble-Metal-Free Photocatalytic Hydrogen Evolution Activity: The Impact of Ball Milling Anatase Nanopowders with TiH2 - Zhou, Xuemei; Liu, Ning; Schmidt, Jochen; Kahnt, Axel; Osvet, Andres; Romeis, Stefan; Zolnhofer, Eva; Marthala, Venkata; Guldi, Dirk Michael; Peukert, Wolfgang; Hartmann, Martin; Meyer, Karsten; et al. (Advanced Materials, 2016)
Ball milling TiO2 anatase together with TiH2 can create an effective photocatalyst. The process changes the lattice and electronic structure of anatase. Lattice deformation created by mechanical impact combined with hydride incorporation yield electronic gap-states close to the conduction band of anatase. These provide longer lifetimes of photogenerated charge carriers and lead to an intrinsic cocatalytic activation of anatase for H2 evolution.
Keywords: Anatase; Ball milling; Hydrogen evolution; Photocatalysis; Titanium hydride